ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI REMAJA PUTRI SMP NEGERI 2 LAUBALENG: MACRONUTRIENT INTAKE AND NUTRITIONAL STATUS OF ADOLESCENT GIRLS OF SMP NEGERI 2 LAUBALENG - Perangin-Angin, Pricillia Adenit Gracia Br; Darungan, Tezar Samekto; Lestari, Ira Cinta; Ain, Nurul (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2025)
Nutrition is a major problem in Indonesia, based on Basic Health Research in 2018, there are still teenagers aged 13-15 years who have insufficient and excessive nutritional status and the same thing also happens in North Sumatra. The aim of this research was to determine the relationship between macronutrient intake and the nutritional status of young women at SMP Negeri 2 Laubaleng. This type of research is analytical observational research with a cross-sectional with a simple random sampling method of 41 samples. Data obtained from the 24 hour Food Recall questionnaire for three weeks. Data analysis used the Sommer's D correlation test, week 1, 2 and 3 macronutrient carbohydrate consumption with week 1, 2 and 3 nutritional status acquire value (p=0.048), (p=0.000), and (p=0.043) , week 1, 2 and 3 macronutrient protein consumption with week 1, 2 and 3 nutritional status acquire value (p=0.004), (p=0.000), and (p=0.043), week 1, 2 and 3 macronutrient fat consumption with nutritional status nutrition week 1, 2 and 3 acquire value (p=0.000), (p=0.000), and (p=0.048). There was a significant relationship in the 3 weeks of observation between macronutrient intake and nutritional status in young women at SMP Negeri 2 Laubaleng. AbstrakGizi menjadi masalah utama di Indonesia, berdasarkan Riset Kesehatan Dasar tahun 2018 masih ada remaja usia 13- 15 tahun yang memiliki status gizi kurang dan berlebih. Hal yang sama juga terjadi di Sumatera Utara. Tujuan penelitian ini adalah untuk mengetahui Hubungan Asupan Zat Gizi Makro dengan Status Gizi Remaja Putri di SMP Negeri 2 Laubaleng. Jenis penelitian ini adalah penelitian observasional analitik, desain potong lintang dengan metode simple random sampling sebanyak 41 sampel. Data diperoleh dari kuesioner Food Recall 24 jam selama 3 minggu. Analisis data menggunakan uji korelasi Sommer’s D, konsumsi zat gizi makro (karbohidrat) minggu 1, 2 dan 3 dengan status gizi minggu 1, 2 dan 3 memperoleh nilai (p=0.048), (p=0.000), dan (p=0.043), konsumsi zat gizi makro (protein) minggu 1, 2 dan 3 dengan status gizi minggu 1, 2 dan 3 memperoleh nilai (p=0.004), (p=0.000), dan (p=0.043), konsumsi zat gizi makro (lemak) minggu 1, 2 dan 3 dengan status gizi minggu 1, 2 dan 3 memperoleh nilai (p=0.000), (p=0.000), dan (p=0.048). Penelitian ini mendapatkan hubungan yang signifikan pada 3 minggu pengamatan antara Asupan Zat Gizi Makro dengan Status Gizi pada Remaja Putri di SMP Negeri 2 Laubaleng.